PERITONITIS BAKTERIAL SPONTAN PADA SIROSIS HATI DAN HUBUNGANNYA DENGAN BEBERAPA FAKTOR RISIKO - Ayu Yuli Gayatri, Anak Agung; Wibawa, I Dewa Nyoman (journal of internal medicine; Vol. 7, No. 2 Mei 2006, 2012)
Spontaneous Bacterial Peritonitis (SBP) is a frequent and severe complication in cirrhotic patients with ascites. It occurs in 10-30% of cases and assosiated mortality rate is 20-40%. Spontaneous Bacterial Peritonitis is diagnosed base on the presence of a Polymorphonuclear leucocyte count greater than 250/mm3 or positive monomicrobial ascitic fluid culture. The key to successful treatment of SBP is knowledge of appropriate antibiotic regimen and an understanding of the setting in wich infection develops, particularly those individuals at high risk of infection. This study was conducted to know prevalence of SBP and to evaluate possible risk faktors for this complication such as: severe cirrhosis (Child C), upper gastrointestinal bleeding, low protein ascites (<1g/dL) and low platelet count (<98.000/mm3). Sixty two consecutive hospitalized patients with cirrhotic and ascites were follow up for manifestations of SBP. Prevalence of SBP was 30.6%. Multivariate analysis and Logistic regression showed that only severe cirrhosis (Child C) is the risk faktor of SBP. (OR= 5.297; 95% CI=1.036-27.079).
Keywords: Spontaneous Bacterial Peritonitis, prevalence, risk factors